Economic analysis and comparison of chemical heat pump systems - Karaca, F; Kincay, O; Bolat, E (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
Over the last years great interest has been shown in chemical heat pump systems. Chemical heat pumps represent a new technology with great potential to reduce the energy consumption in very different sectors. They can provide the ability to capture the rejected low-grade heat and to reuse it at increased temperature levels in various industrial processes. Heat can be removed from a heat source at low-temperature by an endothermic reaction and can be boosted to a heat sink at high-temperature by an exothermic reaction. Since chemical heat pumps can operate without compression, with less electrical power and at higher temperature levels compared to conventional heat pumps, they can afford high performance advantages. As an additional advantage, energy storage can also be accomplished so that intermittent energy sources can be utilized in a chemical heat pump system. The objective of this work was to study methanol-formaldehyde-hydrogen, ethanol-acetaldehyde-hydrogen, i-propanol-acetone-hydrogen and n-butanol-butyraldehyde-hydrogen chemical heat pump systems based on catalytic dehydrogenation of alcohols at low-temperature and hydrogenation of aldehydes-and a ketone at high-temperature. On the base of economic analysis, the quantity of waste-heat that must be supplied to produce the benefits of the process heat and also the improvement in the net gain reached were determined and compared. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: chemical heat pump; dehydrogenation of alcohols; hydrogenation of aldehydes and ketone; economic analysis; DEHYDROGENATION; 2-PROPANOL; Thermodynamics; Energy & Fuels; Engineering; Mechanics